EKSPERIMENTASI MODEL PEMBELAJARAN DISCOVERY LEARNING, PROBLEM BASED LEARNING, DAN THINK PAIR SHARE DENGAN PENDEKATAN SAINTIFIK TERHADAP KOMPETENSI PENGETAHUAN DAN SIKAP SOSIAL DITINJAU DARI GAYA BELAJAR SISWA - Pinahayu, EK Ajeng Rahmi; Mardiyana, Mardiyana; Slamet, Isnandar (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aim of this research was to find out the different effects of Discovery Learning (DL), Problem Based Learning (PBL), and Think Pair Share (TPS) models with scientific approach towards students knowledge and social attitude competency viewed from the students learning styles. This study was a quasi-experimental research. The population of research was all of the 8th grade of the State Junior High School in Puworejo Regency on the second semester of 2014/2015 academic year. The hypothesis testing of research were conducted using a two-ways multivariate analysis of variance with different cells. The conclusions of this research were as follows. (1) DL provided better knowledge competency than PBL and TPS, while PBL and TPS was same. (2) DL and TPS provided same social attitude competency, and both provided better social attitude competency than PBL. (3) The knowledge competency of visual students was better than auditory and kinesthetic, and the knowledge competency of students in those types was same. (4) The social attitude competency of visual and auditory students was same, the social attitude competency of visual students was better than kinesthetic, the social attitude competency of auditory and kinesthetic students was same. (5) In DL, the knowledge competency of visual students was better than auditory, the knowledge competency of visual students was better than kinesthetic, the knowledge competency of auditory and kinesthetic students was same. In PBL and TPS, the knowledge competency of visual, auditory, and kinesthetic students was same. (6) In DL and TPS, the social attitude competency of those three types was same. In PBL, the social attitude competency of visual students was better than auditory, the social attitude competency of visual and kinesthetic students was same, the social attitude competency of auditory and kinesthetic students was same. (7) In visual, DL provided better knowledge competency than PBL and TPS, PBL and TPS provided same knowledge competency. In auditory and kinesthetic, DL, PBL, and TPS provided same knowledge competency. (8) In visual and kinesthetic, DL, PBL, and TPS provided same social attitude competency. In auditory, DL and PBL provided same social attitude competency, DL and TPS was same, and TPS provided better social attitude competency than PBL.Keywords: Discovery Learning, Problem Based Learning, Think Pair Share, Scientific Approach, Knowledge Competency, Social Attitude Competency, Learning Styles.